Nature-based credit markets at a crossroads - Swinfield, T; Shrikanth, S; Bull, JW; Madhavapeddy, A; zu Ermgassen, SOSE (Springer Nature, 2024)
Continuing to produce nature-based credits using dubious accounting methodologies will yield limited carbon and biodiversity gains. Establishing scientific credibility unlocks the potential of credits to meaningfully contribute to targets of the Paris and Kunming-Montreal agreements.